Energy-Efficient Distillation Processes by Additional Heat Transfer Derived From the FluxMax Approach - Schack, Dominik; Jastram, Alexander; Liesche, Georg; Sundmacher, Kai (Frontiers in Energy Research, 2020)
Distillation processes are an essential component of any chemical plant for the separation and purification of condensable mixtures. However, distillation columns account for the largest contribution to the total energy consumption of chemical processes due to their high heat demands. Consequently, there is a strong need for energy efficient column designs to reduce drastically the carbon dioxide emissions and thus to reach the settled climate goals of the chemical industry. In this paper the FluxMax approach is used to identify energy optimal column designs. The representation of the distillation process by the elementary processes mixing, heating/cooling and phase separation leads to increased degrees of freedom of optimization compared to classical column modeling approaches. In this way, a non-conventional design with minimal energy consumption is identified. The energy-optimized configuration is a column with improved heat transfer between vapor and liquid streams. MESH equations are used for the validation of the FluxMax design, as they are state-of-the-art in process modeling tools. While the new design reduces the energy demand by up to 64 % compared to the classical design, additional heat exchange area is required to exploit the energy reduction potential. A multi-objective optimization – energy duty vs. heat exchanger area – is carried out to identify the optimal trade-off between energy demand and heat exchanger area related capital cost. The highly energy-efficient designs identified by the FluxMax approach may be realized in practice by horizontal columns or modularized container solutions.